PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIb SMP NEGERI 23 PEKANBARU - Aulya Gusty Maretha; Putri Yuanita; Armis Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action research which aims to improve the learning process and the result of learning mathematics by applying problem based learning (PBL) model. The research consist of two cycle. The subject of this research is student of class VIIb SMP Negeri 23 Pekanbaru in the second semester of the 2018/2019,which amountted to 40 students, there are 24 female students and 16 male students. Instruments on this reserach constisted of syllabus, lesson plans and worksheets, and instruments of data collection which is observation sheets and the test result sheets. The function of observation sheet is to obtain data from the learning process, while the function of results sheet of the mathematics learning tests is to obtain the results of the study. The data obtained are then analyzed by the technique of analyzing the data of teacher and student activities as well as data analysis of student mathematics learning outcomes with descriptive statistical analysis. On the knowledge competence, from the basic score of 24 students or 60% increased to 26 students or 66,24% in the first cycle and increased to 32 students or 76,92% in Cycle II. On the skills competence, the number of students who reach the minimum criteria of mastery learning from Cycle I of 16 students or 63,72% improve to 35 students or 86,85% in cycle II.. The results of this analysis indicate that the implementation of the PBL model can improve the learning achievement students of class VIIb SMP Negeri 23 Pekanbaru academic year 2018/2019.Key Words: Classroom Action Research, Problem Based Learning models, Learning outcomes